HUBUNGAN REGULASI EMOSI DENGAN DISMENORE PADA REMAJA DI ERA PANDEMIK COVID 19 - Mirza, Mirza; Kusumasari, Viantika; Riyadi, Muskhab Eko (Jurnal Medikes (Media Informasi Kesehatan), 2022)
The high incidence of dysmenorrhea in adolescents has not received attention from adolescents themselves and society in general. Dysmenorrhea makes teenagers unable to carry out normal activities and concentrate on learning. One of the risk factors that cause dysmenorrhea is poor emotional regulation. This study aims to determine the relationship between emotion regulation and dysmenorrhea in adolescents. The design of this research is cross-sectional, sampling with a total sampling technique. The sample size is 128 young women in class XI at MAN 3 Bantul. The study was conducted from September 28 to October 16, 2020. This study used two research instruments, namely the emotional regulation scale questionnaire to measure emotion regulation and the Numeric Rating Scale (NRS) to measure dysmenorrhea. The statistical test used the Chi-Square test. The result of this research is emotion regulation in adolescent girls mostly in the good category as many as 68 respondents (53.1%). Dysmenorrhea in adolescent girls is mostly in the category of moderate dysmenorrhea among as many as 64 respondents (50.0%). Based on the chi-square test, a p-value of 0.016 was obtained, which means that there is a relationship between emotional regulation and dysmenorrhea in adolescents. Suggestions to adolescents for the need to improve emotional regulation and pay attention to other factors that cause dysmenorrhea.